Exploring a Culture with UNESCO 2030 Objectives and SWOT The Mayangna of Nicaragua - Lane, Paul; Salazar, Ernesto Gómez (Advances in Social Sciences Research Journal, 2018)
An exploration into one of Central America’s indigenous nations using a UNESCO 2030 Objective and a business SWOT. The authors have visited the Mayangna people and read about them as part of the empathy process. They are doing this with the hope of eventually creating a culturally sensitive program to help the Mayangna leadership achieve whatever goals they set for their nation and for their communities. This is a special region of a special country and quite remote from the typical tourist destinations. Through the work with the Autonomous University of the Caribbean Coast, introductions and access were obtained to the Sumu-Mayangna Nation. This work explores with one Indigenous Nation but there are more than 77 million Indigenous and Afro descendent persons in Latin America and Caribbean alone. Estimates are that there are 45,000,000 indigenous persons in more 800 different groups in Latin America. There are about 7.5 million Indigenous persons in Central America. In Nicaragua, the estimate is 520,000. In this paper, the focus is on one group with a methodology that may be helpful in assessing other indigenous groups in the future. The paper is an exploration of what we know to date in June 2018. The goal is to build to a multi-university interdisciplinary program working with the indigenous communities to accomplish the goals of those communities.